Supervisi dalam Peningkatan Mutu Evaluasi Pembelajaran di Sekolah Dasar Negeri 114 Rejang Lebong - Enilawati; Warlizasusi, Jumira; Harahap, Emmi Kholilah (Ta lim Jurnal Pendidikan Agama Islam dan Manajemen Pendidikan Islam, 2022)
To improve the quality of learning, supervision is necessary. Supervision needs to cover the entire learning program which consists of planning, implementation, and evaluation or final assessment in learning. The assessment of the learning design includes aspects of developed competencies, selected learning strategies, and program content. Assessment of the implementation of learning programs seeks to assess how high the level of quality of learning is carried out by teachers. Assessment of the results of the learning program is not limited to short-term results or outputs but should also reach the outcomes of the learning program. This research uses descriptive qualitative method. With only 7 teachers and 93 students, and schools without internet access. The results showed that the State Elementary School 114 Rejang Lebong carried out supervision as an effort to improve the quality of learning evaluation.